Meningkatkan Berpikir Kritis Siswa Katolik dengan Model Pembelajaran Problem Based Learning (PBL) Berbantuan Media Video Meteri Suara Hati Kelas X SMA Negeri 1 Bandar Khalipah - Irvan Arvandi Sitohang (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Something that should be thanked to the Holy Trinity (God the Father, God the Son and God the Holy Spirit) God Almighty, with the policy of the Government, especially the Minister of Education and Culture (Kemendikbud) to publish the lesson books, including the lesson books for Catholic Religious Education and character. Apart from the researcher's gratitude for the publication of Catholic Religious Education and Books, the researcher also as one of the Teachers of Catholic Religious Education and character for the High School Level, that education plays an important role for the development of human for the better life , in terms of critical thinking. However, in realizing Catholic Religious Education and ethics to students, there are still many problems, one of the weakness is, the students' critical thinking skills which has an impact on decreasing their learning outcomes in class. Researcher as the teacher try to solve the problem which is faced in the classroom with a variety of learning models, one of the learning model which is used by the researcher is PBL (Problem Based Learning) .This learning model is implemented by two cycles ,that starting on Friday, September 13, 2024. Hopefully by applying this PBL model which is assisted by the video, can improve the Critical thinking of grade X Catholic students at SMA Negeri 1 Bandar Khalipah , in accordance with the vision and mission of the school and one of the objectives of National education, namely the formation of the Pancasila Student Profile (P3) character contained in the independent curriculum that is being promoted by the current government through the education minister of the Republic of Indonesia, namely Nadiem Anwar Makarim, B.A., M.B.A.